Global brain analysis of minor hallucinations in Parkinson’s disease using EEG and MRI data - Liu, Chuan; Qu, Liangcheng; Li, Qixue; Cao, Yiting; Shi, Jingping; Yu, Chao; Liu, Weiguo; Yin, Kuiying (Frontiers in Aging Neuroscience, 2024)
Visual hallucination is a prevalent psychiatric disorder characterized by the occurrence of false visual perceptions due to misinterpretation in the brain. Individuals with Parkinson's disease often experience both minor and complex visual hallucinations. The underlying mechanism of complex visual hallucinations in Parkinson's patients is commonly attributed to dysfunction in the visual pathway and attention network. However, there is limited research on the mechanism of minor hallucinations. To address this gap, we conducted an experiment involving 13 Parkinson's patients with minor hallucinations, 13 Parkinson's patients without hallucinations, and 13 healthy elderly individuals. We collected and analyzed EEG and MRI data. Our findings revealed that Parkinson's patients with minor hallucinations exhibited excessive activation of cortical excitability, an imbalanced interaction between the attention network and the default network, and disruption in the connection between these networks. These findings is similar to the mechanism observed in complex visual hallucinations. Furthermore, we utilized EEG data from abnormal brain regions to train a machine learning model to determine whether the abnormal EEG data were associated with minor hallucinations. The results demonstrated significant differences between Parkinson's patients with hallucinations and healthy subjects.